Preparation, mechanical properties and wear behaviors of novel aluminum bronze for dies - 李文生 王智平 路阳 高勇 徐建林 (Transactions of Nonferrous Metals Society of China, 2006)
A modified single melt technique involving joint charging was developed for preparation of aluminum bronze, Cu-14%Al-X（mass fraction） alloy, which could be used as die materials. The mechanical properties and wear behavior of the developed alloy under boundary-lubrication conditions was investigated. The results demonstrate that all the phases disperse homogeneously in the bronze matrix with a significant amount of discrete and spherical brittle and hard γ2 phase, moreover, the dispersed k phase are the dominant factor that improves the anti-deformation properties of the soft matrix, after a solution treatment at 920 ℃ for 2 h and followed by aging at 580 ℃ for 3 h, thus remarkably improves the mechanical properties and wear resistance of the developed alloy. The Cu-14%Al-X alloy can be used as materials for static precise stretching and squeezing dies.